Tropopause height at 78 degrees N 16 degrees E: average seasonal variation 2007-2010 - Hall, Chris; Hansen, Georg Heinrich; Sigernes, F; Kuyeng, Karim (Atmospheric Chemistry and Physics, 2011)
We present a seasonal climatology of tropopause altitude for 78° N 16° E derived from observations 2007–2010 by the SOUSY VHF radar on Svalbard. The spring minimum occurs one month later than that of surface air temperature and instead coincides with the maximum in ozone column density. This confirms similar studies based on radiosonde measurements in the arctic and demonstrates downward control by the stratosphere. If one is to exploit the potential of tropopause height as a metric for climate change at high latitude and elsewhere, it is imperative to observe and understand the processes which establish the tropopause – an understanding to which this study contributes.